Effect of Gokhru Plant Extract on Intestinal Absorption of Aspirin using Everted Sac Technique - SEN, SAIKAT (International Journal of Pharmaceutical & Biological Archive, 2011)
Permeability through biological membranes is a key factor in the absorption and distribution of drugs. Aspirin on oral absorption undergo extensive presystemic metabolism, therefore it requires high and frequent dosing which is related with an increased risk of GIT side-effects. The present study aimed to investigate effect of Gokhru plant (Tribulus terrestris Linn.) extract on intestinal absorption by everted sac technique using goat intestine. When Aspirin kept with Gokhru plant extract, the concentration of absorbed Aspirin was 9, 14, 16, 18, 24 Î¼g/ml after 15, 30, 45, 60 and 75 min respectively; where as 8, 10, 13, 15, 20 Î¼g/ml of Aspirin absorbed when kept alone. The study clearly showed that the Gokhru extract enhance the absorption of Aspirin from goat intestine and the absorption enhancement activity of the plant may due to presence of saponin in the extract.